Economic Geology Models 3. Geological Contributions to Geometallurgy: A Review - Hunt, J.; Berry, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2017)
Geometallurgy is a cross-disciplinary science that addresses the problem of teasing out the features of the rock mass that significantly influence mining and processing. Rocks are complex composite mixtures for which the basic building blocks are grains of minerals. The properties of the minerals, how they are bound together, and many other aspects of rock texture affect the entire mining value chain from exploration, through mining and processing, waste and tailings disposal, to refining and sales. This review presents rock properties (e.g. strength, composition, mineralogy, texture) significant in geometallurgy and examples of test methods available to measure or predict these properties.Geometallurgical data need to be quantitative and spatially constrained so they can be used in 3D modelling and mine planning. They also need to be obtainable relatively cheaply in order to be abundant enough to provide a statistically valid sample distribution for spatial modelling. Strong communication between different departments along the mining value chain is imperative so that data are produced and transferred in a useable form and duplication is avoided. The ultimate aim is to have 3D models that not only show the grade of valuable elements (or minerals), but also include rock properties that may influence mining and processing, so that decisions concerning mining and processing can be made holistically, i.e. the impacts of rock properties on all the cost centres in the mining process are taken into account. There are significant costs to improving ore deposit knowledge and it is very important to consider the cost-benefit curve when planning the level of geometallurgical effort that is appropriate in individual deposits.